2013
DOI: 10.1371/journal.pone.0066030
|View full text |Cite
|
Sign up to set email alerts
|

Does Integrated Management of Childhood Illness (IMCI) Training Improve the Skills of Health Workers? A Systematic Review and Meta-Analysis

Abstract: BackgroundAn estimated 6.9 million children die annually in low and middle-income countries because of treatable illneses including pneumonia, diarrhea, and malaria. To reduce morbidity and mortality, the Integrated Management of Childhood Illness strategy was developed, which included a component to strengthen the skills of health workers in identifying and managing these conditions. A systematic review and meta-analysis were conducted to determine whether IMCI training actually improves performance.MethodsDa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 80 publications
4
73
0
2
Order By: Relevance
“…With the exception of two studies that successfully improved CHW stock continuity through training of health facility pharmacists,35,42 it was not always clear to what extent such intervention had been effective. A recent systematic review and meta-analysis concluded that training in integrated management of childhood illnesses could improve quality of treatment of childhood illnesses at health facility level, particularly when implemented in conjunction with greater supervision 59. The variety of challenges for those studies in this review that did not have intensive involvement of a research team also support that training alone is insufficient to improve health system capacity; more in-depth assessment of the needs at the supervising health facility level will be needed to design appropriate interventions to support CCM.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of two studies that successfully improved CHW stock continuity through training of health facility pharmacists,35,42 it was not always clear to what extent such intervention had been effective. A recent systematic review and meta-analysis concluded that training in integrated management of childhood illnesses could improve quality of treatment of childhood illnesses at health facility level, particularly when implemented in conjunction with greater supervision 59. The variety of challenges for those studies in this review that did not have intensive involvement of a research team also support that training alone is insufficient to improve health system capacity; more in-depth assessment of the needs at the supervising health facility level will be needed to design appropriate interventions to support CCM.…”
Section: Discussionmentioning
confidence: 99%
“…These scoring systems, which generally include multiple clinical parameters, have been evaluated in middle income countries such as Brazil, 13, 14, 17 , Egypt, 13 , Latvia and Croatia, 15 but it is not known whether they are applicable, feasible, or practical for use in the less developed countries of sub-Saharan Africa where overall implementation of recommended guidelines for clinical care is known to be inadequate. 18, 19 After searching for a simplified approach, we found that a single finding, tender cervical lymph nodes, could identify 89.8% of GAS-positive children with sore throat and when absent could avoid unnecessary antibiotics administration in 28.2% of GAS-negative children. Cervical adenopathy (variously defined as enlargement and/or tenderness) has improved the sensitivity of most decision rules (although not to the extent that we observed) and has been incorporated into numerous models.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the personal characteristics of community health workers can be associated with their performance [8,11,15,27], suggesting that the CBDs to be trained should be carefully selected [11,28]. However, recent reviews reveal that results, particularly with regard to performance compared by type and sex, are not always consistent [12], and that "studies of workers with lower baseline performance showed greater improvements in prescribing medications…, vaccinating children,… and counseling…" [29]. As well, the more educated CBDs, who are traditionally more productive, are also less committed and more likely to drop out [8,11,15,27].…”
Section: Discussionmentioning
confidence: 99%